Two English Teachers’ Narratives of Professional Growth: Major Stories and Critical Events - Prihendriani, Vivi (Beyond Words, 2023)
The academic journey for advanced degree is challenging. It reflects the professional endeavours of those who take the route. This study explored life-stories of two EFL teachers who were pursuing their advanced degree (doctoral degree) for their career advancement.  The guiding question for this inquiry is related to the stories and challenges and the impacts of the challenges on the participants’ professional growth. The data were collected in the form of narratives from interviews with the two participants. Supporting documents related to the participants’ experiences were also collected. The data were analysed in the framework of critical event analysis. Thus, the life-stories of the participants were identified in terms of episodes and events. The major stories of challenges were identified by looking at the emerging themes. The transformation and changes in their professional identities were identified by looking at the critical events intertwining in the narratives. The narratives of the two participants indicated that the challenges they faced have contributed to their professional transformation as teachers and researchers.